Validated stability-indicating RP-HPLC assay method for fesoterodine fumarate in pharmaceutical products - Onur PINARBASLI; Tolga OZBAY; Gulistan Pelin GURBETOGLU; Nagehan SARRACOGLU; Asuman DOGANAY (Polskie Towarzystwo Farmaceutyczne, 2023)
The goal of the current study was to develop a precise, sensitive and validated reverse phase HPLC method for determination of fesoterodine fumarate (FST). The current investigation was performed for a stability indicating method in order to obtain both assay and impurity profiles of FST. All the experiment was done on HPLC Shimadzu Prominence 20A having stainless steel ACE5 C18 column with a particle size of 5µm and a dimension of 4.6 mm X 150 mm. The mobile phase was in gradient mode with mobile phase A (0.03M ammonium acetate buffer : acetonitrile : methanol (55:30:15 v/v) pH 3.8) and mobile phase B (water) . The flow rate was 1.2 mL/min and the wavelength 208 nm was selected for detection. This method was validated for linearity and range, accuracy, precision and robustness in accordance with ICH requirements. The retention time of fesoterodine was found as 11.0 min. The main degradation product 5-hydroxymethyltolterodine (5-HMT; active metabolite of FST) and the other process impurities; aldehyde, benzylated hydroxy, tolterodine ester, diester impurities were detected easily at the retention times 3.8, 13.5, 16.7, 21.5, 37.1 minutes, respectively. It was observed that the retention times of the main peak and its impurities were not affected and the selectivity of the method was proved under the applied stress conditions. With this developed method, FST and its impurities can easily be detected. It is also stable, simple, accurate, and completely validated RP-HPLC technique for the analysis of FST and related impurities that meets with ICH standards.